Development and evaluation of polyclonal antibody-based enzyme-linked immunosorbent assay for the detection of trichomonas vaginalis in vaginal swabs - Ong, Vanissa A. (Institute of Biology, College of Science, University of the Philippines Diliman, 2009)
Trichomoniasis, caused by the protozoan parasite, trichomonas vaginalis, is the most prevalent nonviral sexually transmitted infection in the world, with an estimate 170 million cases per year. Infection with trichomonas vaginalis is associated with prenatal complications and increased incidence of HIV transmission.